Long-acting anti-fouling heat-conducting and heat-dissipating coating composite coating and preparation method thereof

By applying a long-term anti-fouling and heat-sinking coating composite coating on electrical equipment, the base coating composed of organopolysilazane precursor, fluorosilicone resin and nanocarbon materials is used to form a thermal mesh chain and a thermal path, which solves the problem of equipment heat and dust adsorption, and achieves long-term anti-fouling and excellent thermal conductivity and heat-sinking properties.

CN119823648APending Publication Date: 2025-04-15NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510106528.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of heat and dust absorption generated by electrical equipment during operation, resulting in reduced equipment operation efficiency and shortened service life.

Method used

A long-term anti-fouling and heat-sinking coating composite coating is adopted, including a primer and a topcoat. The primer is composed of an organopolysilazane precursor, fluorosilicone resin, graphene material, carbon nanotubes, etc., and a dense thermal mesh chain and thermal path are formed through electrostatic spraying process.

Benefits of technology

It achieves long-term anti-fouling and excellent thermal conductivity and heat dissipation performance, extends the service life of the equipment and improves operating efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255615920000151
    Figure BDA0005255615920000151
  • Figure BDA0005255615920000161
    Figure BDA0005255615920000161
  • Figure BDA0005255615920000162
    Figure BDA0005255615920000162
Patent Text Reader

Abstract

The invention provides a long-acting anti-fouling heat-conducting and heat-dissipating paint composite coating and a preparation method thereof. The long-acting anti-fouling heat-conducting and heat-dissipating paint composite coating comprises a bottom coating and a The bottom coating is prepared from the following components in percentage by mass: 15 to 25 percent of organic polysilazane precursor, 4.5 to 5.5 percent of fluorosilicone resin, 1 to 2 percent of graphene material, 0.5 to 1.5 percent of carbon nano tube, 0.5 to 1.5 percent of insulating carbon black, 5 to 10 percent of whisker material, 5 to 10 percent of nano-scale heat dissipation filler, 30 to 40 percent of micron-scale heat dissipation filler, 0.5 to 2 percent of coupling agent, 2 to 4 percent of nonionic polymer dispersant, 6 to 10 percent of pyrrolidone material, 2 to 4 percent of other auxiliaries and the balance of solvent, wherein the total mass of the organic polysilazane precursor and the fluorosilicone resin is 100 percent. According to the invention, by adopting the raw materials of the types and dosage, the composite coating has excellent long-acting anti-pollution and heat dissipation functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a long-lasting anti-fouling, thermally conductive and heat-dissipating coating composite coating and a preparation method thereof. Background Art

[0002] In recent years, with the advancement of science and technology, the rapid development of high-power electrical appliances and electronic products, mechanical equipment, electronic communication equipment, etc. will inevitably generate a lot of heat and dust adsorption during operation. If the heat and dust problems generated by operation are not properly solved, the operating efficiency of the equipment will be reduced, and in severe working conditions, the service life of the equipment will be shortened.

[0003] At present, the main solution on the market for the heat generated by equipment operation is forced heat exchange, that is, installing heat exchangers, radiators and other heat dissipation equipment on the required heat dissipation components. However, the equipment is made of active metal substrates (such as aluminum, copper, etc.), which are prone to oxidation and aging after high temperature and long-term use, which in turn leads to an increase in the interface thermal resistance of the equipment, a deterioration in the cooling and heat dissipation effect, and seriously affects the normal operation and service life of the equipment.

[0004] Regarding the dust problem, since most of the dust in the air is oleophilic or partially charged, it is easy to adsorb on the surface of objects. Dust accumulation on the surface of objects will increase the surface thermal resistance of the object and affect the heat dissipation of the equipment. On the other hand, it will seriously affect the operation safety of the equipment: for example, after serious dust pollution of electronic communication equipment and engines, heat will accumulate during operation, and the equipment will be damaged due to temperature overload. The materials currently available on the market can meet or partially meet the requirements of hydrophobicity, but the durability and oleophobicity of hydrophobicity are difficult to guarantee. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating and a preparation method thereof, wherein the composite coating has long-lasting anti-fouling performance and also has excellent thermally conductive and heat-dissipating performance.

[0006] The present invention provides a long-lasting anti-fouling, heat-conducting and heat-dissipating paint composite coating, comprising a primer coating and a top coating;

[0007] Based on 100% of the total mass, the primer layer includes 15-25% of an organic polysilazane precursor, 4.5-5.5% of a fluorosilicone resin, 1-2% of a graphene material, 0.5-1.5% of a carbon nanotube, 0.5-1.5% of an insulating carbon black, 5-10% of a whisker material, 5-10% of a nanoscale heat dissipation filler, 30-40% of a micron-scale heat dissipation filler, 0.5-2% of a coupling agent, 2-4% of a nonionic polymer dispersant, 6-10% of a pyrrolidone material, 2-4% of other additives, and the remainder of a solvent.

[0008] Preferably, the organic polysilazane precursor is selected from one or more of methyl hydrogen silazane, hexamethylcyclotrisilazane, octamethylcyclotetrasilazane, methyl vinyl silazane, vinyl polysilazane, methyl polysilazane and silicone rubber polysilazane.

[0009] Preferably, the nonionic polymer dispersant is selected from one or more of polyether super dispersants, polyacrylic acid super dispersants and polyolefin super dispersants;

[0010] The coupling agent is selected from one or more of a titanate coupling agent, a polysiloxane coupling agent, a chromate coupling agent and an aluminate coupling agent;

[0011] The pyrrolidone material is selected from N-methylpyrrolidone solvent and / or polyvinylpyrrolidone solution;

[0012] The whisker material is selected from one or more of whisker silicon, aluminum oxide whisker, silicon carbide whisker, boron carbide whisker, zirconium dioxide whisker, aluminum nitride whisker and silicon nitride whisker.

[0013] Preferably, the nanoscale heat dissipation filler is selected from one or more of spinel pigments, aluminum nitride nanoscale materials, aluminum oxide nanoscale materials, silicon nitride nanoscale materials, boron nitride nanoscale materials, silicon carbide nanoscale materials, magnesium oxide nanoscale materials, zinc oxide nanoscale materials, silicon oxide nanoscale materials, barium titanate nanoscale materials and cerium dioxide nanoscale materials;

[0014] The micron-sized heat dissipation filler is selected from one or more of an aluminum oxide micron-sized filler, a boron nitride micron-sized filler and a silicon carbide micron-sized filler;

[0015] Preferably, the other additives include one or more of fluorosilicone surfactants, leveling agents, thixotropic thickeners and defoamers;

[0016] The solvent is selected from one or more of aromatic hydrocarbon solvents, ether solvents and ester solvents.

[0017] Preferably, the raw materials for preparing the top coating layer include, by mass fraction, 70-80% fluorosilicone resin, 1-2% nano anti-graffiti additive, 1-5% other additives and the remainder solvent.

[0018] The fluorosilicone resin is selected from a room temperature self-crosslinking perfluorinated modified polysiloxane resin;

[0019] The nano anti-graffiti additive is a nano anatase titanium dioxide material;

[0020] The other additives are selected from one or more of fluorosilicone leveling agents, defoamers and thickeners;

[0021] The solvent is selected from one or more of aromatic hydrocarbon solvents, ester solvents and alcohol ether solvents.

[0022] The total thickness of the top coating and the primer is 10-15 μm.

[0023] The present invention provides a method for preparing the long-lasting anti-fouling thermal conductive and heat dissipating coating composite coating described in the above technical solution, comprising the following steps:

[0024] Mixing part of the organic polysilazane precursor, fluorosilicone resin, nonionic polymer dispersant, coupling agent, pyrrolidone material, part of the solvent, graphene material, insulating carbon black and carbon nanotubes, dispersing to obtain a dispersed slurry, grinding to a fineness of less than 5 μm, to obtain a first grinding slurry;

[0025] The first grinding slurry and the whisker material, the nano-scale heat dissipation filler, and the micron-scale heat dissipation filler are further ground to a fineness of less than 15 μm to obtain a second grinding slurry;

[0026] The second grinding slurry is mixed with the remaining organopolysilazane precursor, other additives, and the remaining solvent to obtain a primer coating;

[0027] The base coating is electrostatically sprayed and then covered with a top coating to obtain a long-lasting anti-fouling, thermally conductive and heat-dissipating composite coating.

[0028] Preferably, the electrostatic spraying comprises:

[0029] The coating process adopts high-voltage electrostatic spraying technology. The primer coating component is sprayed first, and the charged atomized particles are oriented using the electric field effect and the spray gun to shape the micro-nano papillary structure of the coating.

[0030] Preferably, the caliber of the spray gun is 0.4-0.6 mm.

[0031] The invention provides a long-lasting anti-fouling thermal conductive heat dissipation paint composite coating, comprising a primer and a topcoat; based on 100% of the total mass, the primer comprises 15-25% of an organic polysilazane precursor, 4.5-5.5% of a fluorosilicone resin, 1-2% of a graphene material, 0.5-1.5% of a carbon nanotube, 0.5-1.5% of insulating carbon black, 5-10% of a whisker material, 5-10% of a nano-scale heat dissipation filler, 30-40% of a micron-scale heat dissipation filler, 0.5-2% of a coupling agent, 2-4% of a nonionic polymer dispersant, 6-10% of a pyrrolidone material, 2-4% of other additives and a balance of solvent. The present invention adopts a composite modification of an organic polysilazane precursor with long-lasting anti-fouling, hydrophobic and oleophobic properties and a fluorosilicone resin, and then uniformly mixes them with graphene materials with high thermal conductivity and high emissivity, nano-carbon materials such as carbon nanotubes and nano-scale heat dissipation fillers, and micron-scale heat dissipation fillers to form a dense long-lasting anti-fouling and heat dissipation coating, so that the coating has a continuous, mutually contacting heat-conducting network chain and heat-conducting path, so that the composite coating has both excellent long-lasting anti-fouling and heat dissipation functions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 These are test photos of contact panels of coatings prepared in Example 1 of the present invention and in comparative examples. DETAILED DESCRIPTION

[0033] The present invention provides a long-lasting anti-fouling, heat-conducting and heat-dissipating paint composite coating, comprising a primer coating and a top coating;

[0034] Based on 100% of the total mass, the primer layer includes 15-25% of an organic polysilazane precursor, 4.5-5.5% of a fluorosilicone resin, 1-2% of a graphene material, 0.5-1.5% of a carbon nanotube, 0.5-1.5% of an insulating carbon black, 5-10% of a whisker material, 5-10% of a nanoscale heat dissipation filler, 30-40% of a micron-scale heat dissipation filler, 0.5-2% of a coupling agent, 2-4% of a nonionic polymer dispersant, 6-10% of a pyrrolidone material, 2-4% of other additives, and the remainder of a solvent.

[0035] The present invention uses the above components for curing and film formation of the base coating and forming a continuous heat-conducting path and a heat-conducting network chain, so that the base coating has excellent long-term anti-fouling and heat-dissipating properties, thereby obtaining a composite coating with excellent anti-fouling and heat-dissipating properties.

[0036] The primer provided by the present invention comprises 15-25% of an organic polysilazane precursor, and the specific amount is 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%. The organic polysilazane precursor described in the present invention is also called an organic polysilazane resin. Polysilazane (PSZ) is a type of polymer with Si-N bonds as repeating units in the main chain, which can be divided into two categories: organic polysilazane (OPSZ) and perhydrated polysilazane (PHPS). The organic polysilazane precursor is a Si-NH polymer containing an organic substituent, which contains C-SiO after curing. X Coating; Due to its special structure, polysilazane can be converted into SiCNO, SiCN or silica ceramics under high temperature conditions. The hardness can reach 8H after curing. High temperature baking can reduce carbon residue. Surface characteristics: hydrophobic Si-NH-Si bond, can be cured at room temperature, and the main reactions involved in curing are the hydrolysis and oxidation of Si-NH-Si. At the same time, the Si-NH-Si bond and the -OH on the surface of the substrate react easily, thus bringing good bonding with the substrate. Organic polysilazane precursors and fluorosilicone resin binders with excellent long-term anti-fouling properties are selected for multiple compounding and modification to enhance the coating's long-lasting hydrophobicity and oleophobicity, adhesion, corrosion resistance, flexibility, mechanical strength, etc. The organic polysilazane precursor has the characteristics of high temperature resistance, oxidation resistance, corrosion resistance, insulation, heat insulation, waterproof, anti-graffiti, self-cleaning, low viscosity, low surface energy, solvent-free and super hardness, excellent adhesion to most substrates, long-term natural hydrophobicity with a water contact angle of more than 95°, and the ability to make ultra-thin varnish (usually tens of nanometers to several microns), etc., which give the coating excellent mechanical and chemical stability and good adhesion to the substrate. By introducing hydrophilic, acid- and alkali-resistant nano-scale heat dissipation materials and micron-level heat dissipation fillers, a micro-nano composite structure is formed on the coating surface, and a nano-level hydrophobic heat dissipation coating protective film is formed on the substrate surface.

[0037] The organopolysilazane precursor in the present invention is preferably one or more selected from methyl hydrogen silazane, hexamethylcyclotrisilazane, octamethylcyclotetrasilazane, methyl vinyl silazane, vinyl polysilazane, methyl polysilazane and silicone rubber polysilazane.

[0038] The primer layer provided by the present invention comprises 4.5-5.5% of fluorosilicone resin; the fluorosilicone resin is a self-crosslinking fully fluorinated modified polysiloxane resin at room temperature, which complements the performance of the organic polysilazane precursor, can overcome the shortcomings of the organic polysilazane in hydrophobicity and oleophobicity, and enhance the comprehensive performance of the coating system, such as anti-fouling, anti-corrosion, anti-aging, flexibility, and mechanical strength.

[0039] The fluorosilicone resin described in the present invention can maintain the thermal stability and main chain flexibility of organosilicon, can significantly improve solvent resistance, and achieve a lower critical surface tension than polytetrafluoroethylene. The oleophobic principle of fluorosilicone resin is that the fluorine atoms on the ring surface of its molecular chain form a strong electronegativity, and the alkyl group in the oil has a strong positive charge, thereby forming a strong electrostatic field, and it is difficult for oil molecules to interact with it, thereby achieving an oleophobic effect. Fluorosilicone resin combines the performance characteristics of perfluorinated and siloxane resins at the same time, and utilizes the characteristics of perfluorinated substituents tending to the surface and self-assembling to form a monolayer, so that the critical surface tension of the modified polymer is less than 10mN / m, and it has strong anti-fouling properties such as hydrophobic, oleophobic, and solvent-repellent. It is a polymer material with excellent heat resistance, corrosion resistance, hydrophobic, oleophobic, and dimensional stability. Composited with the organopolysilazane precursor, the performance is complementary, and the shortcomings of the hydrophobic and oleophobic properties of the organopolysilazane can be overcome, and the comprehensive properties of the anti-fouling, corrosion resistance, anti-aging, flexibility, and mechanical strength of the coating system are well enhanced. A thin coating is applied on the surface of the base coating to give the system a good protective effect and meet the requirements of coating stability, weather resistance, and long-lasting anti-fouling.

[0040] The primer provided by the present invention comprises 1-2% of graphene material, and the specific amount is 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%. The graphene material is preferably selected from at least one of single-layer graphene G, few-layer graphene material, and graphene microsheet; the above-mentioned types of graphene materials are all carbon-based materials with high thermal conductivity, and nano-carbon materials such as insulating carbon black and carbon nanotubes can enhance the thermal conductivity and heat dissipation characteristics of the paint film and the shielding and anti-corrosion effect of the coating film; wherein, the thermal conductivity coefficient of the single-layer graphene is 5000W / (mK). The present invention adds nonionic polymer dispersants, pyrrolidone materials, and coupling agents to the coating. Through the joint action of these additives, the dispersion and wetting of graphene / carbon nanotubes are increased, and the dispersion stability of the coating is improved, so that the nano-scale carbon material can play a role in enhancing the thermal conductivity and heat dissipation characteristics of the paint film and the shielding and anti-corrosion effect of the coating film, providing a guarantee for the graphene material to exert the above-mentioned properties.

[0041] The primer provided by the present invention comprises 0.5-1.5% carbon nanotubes, and the specific amount is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%. The carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the axial thermal conductivity of the single-walled carbon nanotubes is 1750-5800 W / (mK). As a quasi-one-dimensional nanomaterial, the carbon nanotubes have extremely excellent thermal conductivity in addition to having a large aspect ratio and excellent mechanical and electrical properties. Using carbon nanotubes with high thermal conductivity as an additive for thermally conductive composite materials can also significantly improve the thermal conductivity of the thermally conductive composite coating. Although carbon nanotubes have good axial heat conduction and heat dissipation characteristics, due to their small size, very large specific surface area and aspect ratio, and the strong electrostatic interaction and van der Waals force between carbon nanotubes, carbon nanotubes are very easy to agglomerate or entangle, which not only affects their function, but also affects the stability and overall performance of the entire coating system. In view of this, the synergistic effect of the non-ionic polymer dispersant, pyrrolidone materials, and coupling agents added to the embodiment coating of the present invention also plays a role in dispersing and wetting the carbon nanotubes, improving the dispersion stability of the coating, so that the carbon nanotubes can play a role in strengthening the thermal conductivity and heat dissipation characteristics of the paint film and the shielding and anti-corrosion effect of the coating film.

[0042] In addition, the graphene and carbon nanotubes used in the present invention have excellent conductive properties. A small amount of addition can make the coating conductive. The conductivity of the coating is in the anti-static range, providing an electrostatic effect for the subsequent electrostatic coating construction of the paint, and the composite coating has the effect of removing static electricity, decontamination and cleaning charged dust during anti-fouling use.

[0043] The base coating provided by the present invention comprises 0.5-1.5% of insulating carbon black, and the specific amount is 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%. The insulating carbon black has the characteristics of high radiation heat dissipation and rapid heat diffusion, and a small amount of addition can greatly accelerate the heat conduction and heat dissipation function of the coating.

[0044] In the present invention, the graphene material, carbon nanotubes and insulating carbon black work together to enhance the heat conduction and heat dissipation characteristics of the paint film and the shielding effect of the coating film. At the same time, the non-ionic polymer dispersant, pyrrolidone material and coupling agent work synergistically on these materials to increase the dispersion and wetting of the graphene material and carbon nanotubes and improve the dispersion stability of the coating, so that these nano-scale carbon materials can play a role in enhancing the heat conduction and heat dissipation characteristics of the paint film and the shielding and anti-corrosion effect of the coating film.

[0045] The primer provided by the present invention comprises 5-10% of whisker material, and the specific amount is 5%, 6%, 7%, 8%, 9% or 10%. The whisker material is selected from one or more of whisker silicon, aluminum oxide whisker, silicon carbide whisker, boron carbide whisker, zirconium dioxide whisker, aluminum nitride whisker and silicon nitride whisker, preferably silicon carbide whisker. The whisker material used in the present invention has good strength and good anti-rust performance, and can be well dispersed in the coating system of the present invention.

[0046] The primer provided by the present invention comprises 5-10% of nano-scale heat dissipation filler, and the specific amount is 5%, 6%, 7%, 8%, 9% or 10%. The nano-scale heat dissipation filler is selected from one or more of spinel pigment, aluminum nitride nano-scale material, aluminum oxide nano-scale material, silicon nitride nano-scale material, boron nitride nano-scale material, silicon carbide nano-scale material, magnesium oxide nano-scale material, zinc oxide nano-scale material, silicon oxide nano-scale material, barium titanate nano-scale material and cerium dioxide nano-scale material; preferably one or more of aluminum oxide nano-scale filler, boron nitride nano-scale filler and silicon carbide nano-scale filler. The nano-scale heat dissipation filler is a filler of sub-nano-particle level and nano-particle size level.

[0047] The base coating provided by the present invention includes 30-40% of micron-level heat dissipation filler, and the specific amount is 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%. The micron-level heat dissipation filler is selected from one or more of alumina micron-level filler, boron nitride micron-level filler and silicon carbide micron-level filler, preferably alumina micron-level filler; the micron-level heat dissipation filler is a micron-level filler with a particle size of less than 15μm. In the embodiment of the present invention, heat dissipation fillers of the same type and different particle sizes are selected. Since the micron-level filler has a relatively high oil absorption and is difficult to disperse, while the micron-level filler has a low oil absorption and is easy to disperse, and the thermal conductivity of the two types of fillers is not much different, a sufficient amount of heat dissipation filler must be added to ensure the heat dissipation effect of the coating; the present invention preferably uses a mixture of heat dissipation fillers of large and small particle sizes to obtain a coating with higher thermal conductivity.

[0048] The present invention adopts the above-mentioned whisker material, nano-scale heat dissipation filler and micron-scale heat dissipation filler combination as the main formula components, so that the paint film has the characteristics of high thermal conductivity and high radiation heat dissipation. The present invention uses fillers of different types and different particle sizes in a certain proportion, which can give full play to the characteristics of a single filler. Due to the hybridization effect, it can not only improve the thermal conductivity, but also strengthen the mutual synergistic effect of multiple thermal conductive fillers. The small particle filler and the whisker with a large aspect ratio are used together. Due to the hybridization effect, the probability of mutual contact between the fillers is increased, and it is easier to form a heat conduction path, which can improve the thermal conductivity of the system more than particles with a single microscopic form.

[0049] The present invention forms a dense long-term anti-fouling and heat-dissipating coating by composite modification of an organic polysilazane precursor with long-term anti-fouling, hydrophobic and oleophobic properties and a fluorosilicone resin, and then uniformly mixing them with graphene materials with high thermal conductivity and high emissivity, nano-carbon materials such as carbon nanotubes and nano-scale heat-dissipating fillers, and micron-scale heat-dissipating fillers, so that the coating has continuous, mutually contacting heat-conducting network chains and heat-conducting pathways, so that the coating has both excellent long-term anti-fouling and heat-dissipating functions.

[0050] The primer provided by the present invention comprises 0.5-2% of a coupling agent, and the specific amount is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%. The coupling agent is selected from one or more of a titanate coupling agent, a polysiloxane coupling agent, a chromate coupling agent and an aluminate coupling agent. The active functional group of the coupling agent can improve the surface properties of graphene and carbon nanotubes, increase the wetting characteristics and hydrophilicity of graphene and carbon nanotubes, and some preferred coupling agents also have a modification effect on graphene materials, so that graphene, carbon nanotubes, etc. can be better dispersed in the resin system.

[0051] The primer layer provided by the present invention comprises 2-4% of a nonionic polymer dispersant, and the specific amount is 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4.0%. The nonionic polymer dispersant is a surfactant selected from one or more of a polyether super dispersant, a polyacrylic acid super dispersant and a polyolefin super dispersant. The nonionic polymer dispersant can be coated on the surface of the graphene material and the carbon nanotube, and can cooperate to modify the surface of the graphene material and the carbon nanotube. Specifically, the nonionic polymer dispersant can cooperate to bind to the large π bonds between the graphene material, such as the graphene particle sheets, which have electrical activity and buffering capacity, to reduce the surface energy of the graphene material, reduce its hard agglomeration, and improve the lubricity and stability of the coating. At the same time, through the bonding action with the π-π bond of the graphene material, the graphene material can be efficiently dispersed in the system under the action of the nonionic polymer dispersant, further improving its stability.

[0052] The primer layer provided by the present invention comprises 6-10% of pyrrolidone materials, and the specific amount is 6%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5% or 10.0%.

[0053] The primer provided by the present invention includes 2-4% of other additives, and the specific amount is 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%. The other additives include one or more of fluorosilicone surfactants, fluorosilicone leveling agents, thixotropic thickeners and defoamers. The fluorosilicone surfactant is selected from one or more of fluorine-modified silicone surfactants, perfluorinated modified silicone surfactants, modified amino fluorosilicone surfactants and polyether modified fluorosilicone surfactants. The fluorosilicone leveling agent is selected from one or more of EFKA3777, WF-F377, LB-F3433 and HyperlevF70N, preferably EFKA3777. The thixotropic thickener is selected from one or more of organic modified bentonite thixotropic agents, hydrophobic fumed silica thixotropic agents, polyamide wax slurry, polyethylene wax slurry and fluorinated wax. The thixotropic thickener in the present invention mainly provides the system with anti-settling and thixotropic thickening effects. The defoamer is selected from one or more of an organosilicon defoamer, an acetylene compound and a mineral oil defoamer.

[0054] The primer layer provided by the present invention includes a residual solvent, and the solvent is a polar solvent and a non-polar solvent that are compatible with the organopolysilazane precursor. The solvent is selected from one or more of aromatic hydrocarbon solvents, alcohol ether solvents, and ester solvents; more preferably, one or more of xylene, butyl acetate, ethylene glycol butyl ether, and propylene glycol methyl ether acetate. In a specific embodiment, the solvent in the primer layer is selected from one or more of xylene, butyl acetate, and propylene glycol acetate.

[0055] In a specific embodiment of the present invention, the raw materials for preparing the primer layer include 15% of organic polysilazane precursor methylhydrogensilazane, 5% of fluorosilicone resin, 2% of 3-10 layers of graphene, 1.5% of multi-walled carbon nanotubes, 0.5% of insulating carbon black, 10% of SIC whisker material, 5% of BN nanoscale heat dissipation filler, 40% of Al2O3 micron-scale heat dissipation filler, 0.5% of hydrophobic fumed silica, and 3% of non-ionic polymer dispersant. VXW 6208 / 60, 2% polysiloxane coupling agent, 6% N-methylpyrrolidone, 1% fluorosilicone leveling agent and 8.5% xylene.

[0056] In one embodiment of the present invention, the raw materials for preparing the primer layer include 20% of organic polysilazane precursor methylhydrogensilazane, 5% of fluorosilicone resin, 1.5% of 3-10 layers of graphene, 1% of multi-walled carbon nanotubes, 1% of insulating carbon black, 5% of SIC whisker material, 10% of BN nanoscale heat dissipation filler, 35% of Al2O3 micron-scale heat dissipation filler, 0.5% of hydrophobic fumed silica, and 4% of non-ionic polymer dispersant. VXW 6208 / 60, 1% polysiloxane coupling agent, 8% N-methylpyrrolidone, 1% fluorosilicone leveling agent and 7% xylene.

[0057] In another embodiment of the present invention, the raw materials for preparing the primer layer include 25% of organic polysilazane precursor methylhydrogensilazane, 5% of fluorosilicone resin, 1% of 3-10 layers of graphene, 0.5% of multi-walled carbon nanotubes, 1.5% of insulating carbon black, 8% of SIC whisker material, 8% of BN nanoscale heat dissipation filler, 30% of Al2O3 micron-scale heat dissipation filler, 0.5% of hydrophobic fumed silica, and 2% of non-ionic polymer dispersant. VXW 6208 / 60, 0.5% polysiloxane coupling agent, 10% N-methylpyrrolidone, 0.5% fluorosilicone leveling agent and 7.5% xylene.

[0058] The long-lasting anti-fouling thermal conductive heat dissipation coating composite coating provided by the present invention also includes a topcoat; the present invention preferably combines the above-mentioned primer with the topcoat composed of the following formula, so that the formed composite coating has better heat dissipation and anti-fouling properties. In terms of mass fraction, the raw materials for preparing the topcoat include 70-80% fluorosilicone resin, 1-2% nano anti-graffiti additive, 1-5% other additives and the balance solvent.

[0059] The fluorosilicone resin accounts for 70-80% of the top coating, and the specific amount is 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%; the fluorosilicone resin in the present invention can maintain the thermal stability and main chain flexibility of silicone, can significantly improve solvent resistance, and achieve a lower critical surface tension than polytetrafluoroethylene. The oleophobic principle of fluorosilicone resin lies in that the fluorine atoms on the ring surface of its molecular chain form a strong electronegativity, and the alkyl group in the oil has a strong positive charge, thereby forming a strong electrostatic field, and it is difficult for the oil molecules to interact with it, thereby achieving an oleophobic effect. Fluorosilicone resin combines the performance characteristics of perfluoro and siloxane resins at the same time, and utilizes the characteristics of perfluoro substituents that tend to the surface and self-assemble into a monolayer, so that the critical surface tension of the modified polymer is less than 10mN / m, and it has strong anti-fouling properties such as hydrophobicity, oleophobicity, and solvent repellency. It is a polymer material with excellent heat resistance, corrosion resistance, hydrophobicity, oleophobicity, and dimensional stability. The compound with the organic polysilazane precursor has complementary properties, which can overcome the shortcomings of the organic polysilazane in hydrophobicity and oleophobicity, and well enhance the comprehensive properties of the coating system such as anti-fouling, anti-corrosion, anti-aging, flexibility, and mechanical strength. A thin coating is applied to the surface of the base coating to give the system a good protective effect, meeting the requirements of coating stability, weather resistance, and long-lasting anti-fouling.

[0060] The nano anti-graffiti agent accounts for 1-2% of the surface layer, and the specific amount is 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; the anti-graffiti agent in the present invention is a nano anti-graffiti easy-to-clean agent based on nanotechnology, which is a nano anatase titanium dioxide material, can be used as a photocatalyst and self-cleaning agent, has antibacterial and mildew-proof properties, and enhances long-term anti-fouling and easy-to-clean properties.

[0061] The other additives in the surface layer account for 1-5%, specifically 1%, 2%, 3%, 4% or 5%. The other additives include one or more of fluorosilicone surfactants, fluorosilicone leveling agents, defoamers and thixotropic thickeners. The fluorosilicone leveling agent is preferably EFKA3777.

[0062] The surface layer includes a residual solvent; the solvent is selected from one or more of aromatic hydrocarbon solvents, ester solvents and alcohol ether solvents, preferably butyl acetate.

[0063] In a specific embodiment of the present invention, the raw materials for preparing the surface layer include 75% fluorosilicone resin, 2% nano anti-graffiti additive, 1% fluorosilicone leveling agent and 22% butyl acetate.

[0064] The fluorosilicone coating varnish of the present invention, the fluorosilicone resin (such as perfluorinated modified polysiloxane) can maintain the thermal stability and main chain flexibility of polysiloxane, can significantly improve the solvent resistance, and achieve a lower critical surface tension than polytetrafluoroethylene. By utilizing the characteristics of the perfluorinated substituents tending to the surface and self-assembling into a monomolecular layer, the fluorosilicone resin obtains better solvent resistance, oil ester resistance, fuel oil resistance, weather resistance, and chemical stability. The fluorosilicone coating varnish is prepared and applied thinly on the surface of the base coating, further improving the stability, weather resistance, and long-term anti-fouling requirements of the composite coating.

[0065] In the long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating provided by the present invention, the total wet film thickness of the base coating and the top coating is 15 to 25 μm; wherein, the wet film thickness of the base coating is 10 to 15 μm; the wet film thickness of the top coating is 5 to 10 μm. The total thickness of the top coating and the base coating after drying is 10 to 15 μm. The optimal waveband for radiant heat dissipation is required to be between 300 nanometers in visible light and 13.5um in near infrared. The total thickness of the top coating and the base coating will affect the heat dissipation. The greater the thickness, the greater the thermal resistance, resulting in difficulty in heat dissipation. The present invention provides a method for preparing the long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating described in the above technical scheme, comprising the following steps:

[0066] Mixing part of the organic polysilazane precursor, fluorosilicone resin, nonionic polymer dispersant, coupling agent, pyrrolidone material, part of the solvent, graphene material, insulating carbon black and carbon nanotubes, dispersing to obtain a dispersed slurry, grinding to a fineness of less than 5 μm, to obtain a first grinding slurry;

[0067] The first grinding slurry and the whisker material, the nano-scale heat dissipation filler, and the micron-scale heat dissipation filler are further ground to a fineness of less than 15 μm to obtain a second grinding slurry;

[0068] The second grinding slurry is mixed with the remaining organopolysilazane precursor and the remaining solvent to obtain a primer coating;

[0069] The base coating is electrostatically sprayed and then covered with a top coating to obtain a long-lasting anti-fouling, thermally conductive and heat-dissipating composite coating.

[0070] The present invention mixes part of organic polysilazane precursor, fluorosilicone resin, nonionic polymer dispersant, coupling agent, pyrrolidone material, part of solvent, graphene material, insulating carbon black and carbon nanotubes, disperses them to obtain dispersed slurry, grinds them to a fineness of less than 5 μm, and obtains a first grinding slurry.

[0071] In the present invention, part of the organopolysilazane precursor in the first polishing slurry accounts for 20-40% of the total amount of the organopolysilazane precursor. The present invention preferably prepares the first polishing slurry in a dispersion tank; the dispersion treatment is preferably stirred at 1000-1500 rpm for 15 minutes. The present invention preferably connects and introduces the dispersed slurry into a nano grinder, and grinds at 1500-2000 rpm for 1-2 hours to a fineness of less than 5 μm.

[0072] The first grinding slurry, whisker material, nano-scale heat dissipation filler, and micron-scale heat dissipation filler are ground for 25 to 35 minutes until the fineness is less than 15 μm to obtain a second grinding slurry.

[0073] The present invention mixes the second grinding slurry with the remaining organopolysilazane precursor and the remaining solvent to obtain a primer coating. The mixing is carried out under stirring conditions; the stirring rate is 800 to 1000 rpm and the time is 20 to 30 minutes. The viscosity of the primer coating component in the present invention is 15 to 35 seconds.

[0074] The primer coating is produced and prepared in a three-step process. Graphene materials, carbon nanotubes and other carbon-based nanomaterials are extremely small particles that are difficult to disperse and stabilize in the system. In order to maximize their intrinsic properties, they must be fully ground and dispersed to ensure the synergistic effect of various materials matched with them and the ultimate stability of the system. The various heat dissipation fillers added later only need ordinary grinding and dispersion to achieve the particle size requirement of 15μm or less in the infrared radiation heat dissipation band required by the system. Finally, the system performance is adjusted to achieve a uniform fluid state to obtain the primer coating component.

[0075] After obtaining the primer coating, the present invention uses electrostatic spraying to coat the primer coating, and then covers it with a coating topcoat coating to obtain a long-lasting anti-fouling, heat-conducting and heat-dissipating composite coating.

[0076] In the present invention, the base coating is preferably electrostatically sprayed and then the micro-nano papillary structure is preferably formed. In the present invention, the top coating is preferably air sprayed.

[0077] In the present invention, the top coating material is preferably prepared according to the following method:

[0078] 70-80% of fluorosilicone resin, 1-2% of nano anti-graffiti additive, 1-5% of other additives and the balance of solvent are evenly dispersed to obtain a top coating paint.

[0079] The top coating coating in the present invention is a long-lasting anti-fouling, hydrophobic and oleophobic coating based on fluorosilicone resin, and the long-lasting anti-fouling, thermally conductive and heat dissipating coating composite coating is used as the main component of the top coating coating. Specifically, the component is used for base coating covering coating.

[0080] The present invention preferably prepares the topcoat paint in another dispersion tank; the fluorosilicone resin, nano anti-graffiti additive, other additives and the remaining solvent are dispersed at high speed until the slurry becomes a uniform fluid state; the high-speed dispersion speed is 1000-1500rpm, and the high-speed dispersion time is 15min.

[0081] The present invention applies the primer coating to the surface of the substrate, and then covers it with the top coating coating. The substrate is selected from the surface of a metal substrate, a plastic substrate, a rubber substrate, a ceramic substrate, and the like.

[0082] The present invention applies the primer coating component to the surface of the object, preferably using a high-voltage electrostatic spraying process, first spraying the primer coating component to perform micro-nano papillary structure modeling, and then air spraying the top coating to cover the top coating component with a thin coating to form a composite coating.

[0083] The electrostatic spraying described in the present invention comprises:

[0084] The coating process adopts high-voltage electrostatic spraying technology. The primer coating component is sprayed first, and the charged atomized particles are oriented using the electric field effect and the spray gun to shape the micro-nano papillary structure of the coating.

[0085] Among them, the caliber of the spray gun used is 0.4~0.6mm.

[0086] Specifically, a high-voltage electrostatic spraying process is used for coating. The primer coating component is sprayed first, and the charged atomized particles are oriented using the electric field effect and a small-caliber spray gun to shape the coating into a micro-nano papillary structure. The top coating is sprayed by air, and after the primer coating is dried, a thin layer of top coating coating component is applied to form a composite coating with hydrophobicity and heat dissipation.

[0087] The theoretical basis of this coating technology is the bionic principle of the "lotus effect": constructing a micro-nano structure (micro-nano papillary structure) with a certain degree of roughness on the surface of solid materials; covering it with a thin layer of material with low surface energy and high weather resistance (fluorosilicone varnish coating) to achieve long-term anti-fouling effect.

[0088] The present invention applies the above-mentioned anti-fouling thermal conductive heat dissipation coating composite coating to the fields of aerospace, semiconductors, photovoltaic cells, high temperature resistant coatings, ceramic materials, resin materials, etc., which can protect the surface of objects from scratches, high temperature, moisture, dirt, corrosion, etc.

[0089] In order to further illustrate the present invention, a long-lasting anti-fouling thermal conductive heat dissipation coating composite coating and a preparation method thereof provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0090] Example 1

[0091] A long-lasting anti-fouling, thermally conductive and heat-dissipating coating composite coating, the formula of which is as shown in the primer coating components of Example 1 in Table 1.

[0092] The preparation method of the long-lasting anti-fouling thermal conductive heat dissipation coating composite coating primer coating comprises the following steps:

[0093] According to the preparation of the primer coating composition of Example 1 in Table 1, 10 parts of the organic polysilazane precursor methylhydrogensilazane, 5 parts of fluorosilicone resin, and 3 parts of nonionic polymer dispersant were added into the dispersion tank according to the formula weight. VXW6208 / 60, 2 parts of polysiloxane coupling agent KH550, 6 parts of N-methylpyrrolidone solvent, 5 parts of xylene, 0.5 parts of insulating carbon black, 2 parts of 3-10 layer graphene material, 1.5 parts of multi-walled carbon nanotubes, stir at a high speed of 1500rpm for 15 minutes, then connect and introduce the dispersed slurry into a nano grinder, grind at a high speed of 2000rpm for 1.5h to obtain the first grinding slurry.

[0094] Then add 10 parts of SiC whisker material, 5 parts of BN nano-scale heat dissipation filler, and 40 parts of Al2O3 micron-scale heat dissipation filler of the formula components into the dispersion tank, continue to grind at a high speed of 2000 rpm for 1 hour, test the fineness of the grinding slurry to less than 15 μm, and prepare the second grinding slurry.

[0095] The second portion of the grinding slurry was exported to another dispersion tank, and 5 portions of organic polysilazane precursor methyl hydrogen silazane, 0.5 portions of hydrophobic fumed silica H15, 1 portion of fluorosilicone leveling agent EFKA3777, and 3.5 portions of xylene were added. The mixture was dispersed at a medium speed of 1000 rpm for 20 minutes until the slurry became a uniform fluid state. Samples were taken for testing and the product was adjusted to a predetermined fineness and viscosity to obtain a primer coating component.

[0096] The preparation method of the long-lasting anti-fouling thermal conductive heat dissipation coating composite coating top coating coating comprises the following steps:

[0097] The top coating component was prepared according to Table 1. According to the formula mass parts, 75% of the fluorosilicone resin, 2% of the nano anti-graffiti additive nano anatase titanium dioxide, 1% of the fluorosilicone leveling agent EFKA3777, and 22% of butyl acetate were added into another dispersion tank. The mixture was dispersed at a high speed of 1500 rpm for 15 minutes until the slurry became a uniform fluid state to obtain the top coating component.

[0098] The coating process of the long-lasting anti-fouling thermal conductive heat dissipation coating composite coating comprises the following steps:

[0099] The following is the coating process of composite coating paint:

[0100] The surface treatment of the coating substrate is carried out in accordance with GB / T 9753-2008 "Electrostatic spraying method for paints and varnishes". The substrate surface mentioned here refers to the surface of a metal substrate, a plastic substrate, a rubber substrate, a ceramic substrate, etc. The following description is mainly based on the metal substrate. The surface is treated in accordance with: GB / T 30790.4-2014: Paint and varnish protective coating systems for anti-corrosion protection of steel structures Part 4: Surface types and surface treatment.

[0101] 1. Roughening: Grind or sandblast the surface of the substrate before coating to remove rust, dust, dirt, etc. attached to the surface of the metal substrate. The roughened surface should reach Sa2.5 level.

[0102] 2. Cleaning: Use special cleaning agent or degreasing agent to remove oil, dust, etc. remaining on the roughened surface.

[0103] 3. Drying of substrate: Before coating, ensure that the surface of the substrate is dry and clean.

[0104] Base coat paint spraying:

[0105] 1. Paint mixing: This product is a single component, filter through a 120-mesh sieve for later use.

[0106] 2. Paint coating and modeling: Use electrostatic spraying method, 0.5mm caliber electrostatic spray gun for spraying, add about 15% of the total amount of paint to dilute the supporting solvent xylene, adjust the viscosity of the paint to 20S to coat four cups, and the spraying distance is about 40cm, which is suitable for electrostatic spraying. Utilize the electric field effect, adjust the power supply voltage of the electrostatic spray gun to 60kv, the air pressure to 0.8MPa, adjust the discharge amount and gas output, and the paint is atomized into particles through the nozzle and then sprayed out. Due to the action of the electric field, it is deposited on the surface of the workpiece, and the flow leveling of the particles and the wet film thickness are controlled to be about 25μm. The heat flow direction of the coating should be parallel to the direction of the coating thermal conductive network chain to produce a micro-nano papillary structure coating of the base coating, and the dry film thickness of the coating should be less than 15μm.

[0107] 3. Curing and drying: After spraying, the surface is cured at room temperature for 1 hour, and the actual drying time is more than 48 hours. It can also be heated at 200℃ for 20 minutes for rapid curing;

[0108] Topcoat paint spraying:

[0109] 1. Paint mixing: This product is a single component, filter with a 120-mesh sieve for later use.

[0110] 2. Paint coating: Use air spraying, 0.5mm caliber spray gun, add about 10% of the total amount of paint solvent butyl acetate to dilute the paint to a viscosity of 15S, apply four cups, air pressure 0.8MPa, evenly apply on the surface of the base coating, wet film 10μm, the dry film thickness of the coating should be less than 5μm.

[0111] 3. Curing and drying: After spraying, the surface is cured at room temperature for 2 hours and the actual drying time is more than 48 hours. It can also be heated at 200℃ for 20 minutes for rapid curing.

[0112] In the embodiment of the present invention, the fineness of the primer coating component is less than 15 μm, and the viscosity is 15 to 35 s / cm3.

[0113] In the embodiment of the present invention, the fineness of the top coating component is less than 5 μm, and the viscosity is 15 to 35 s / cm3.

[0114] In the embodiment of the present invention, the designed thickness of the composite coating is about 20 μm, so as to form a coating thickness suitable for a better infrared radiation band.

[0115] Example 2

[0116] A long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating, the base coating coating formula components are shown in Example 2 in Table 1, and the preparation method thereof refers to Example 1.

[0117] The top coating composition is shown in Table 1.

[0118] The coating process of the composite coating refers to the coating process of the composite coating paint in Example 1.

[0119] Example 3

[0120] A long-lasting anti-fouling thermal conductive heat dissipation coating composite coating, the base coating coating formula components are shown in Example 3 in Table 1. The preparation method thereof is referred to Example 1.

[0121] The top coating composition is shown in Table 1.

[0122] The coating process of the composite coating refers to the coating process of the composite coating paint in Example 1.

[0123] Table 1

[0124]

[0125]

[0126] The performance of the base coating of the long-lasting anti-fouling thermal conductive and heat dissipating coating composite coating prepared in Example 1, Example 2, and Example 3 was tested, and the test results are shown in Table 2.

[0127] Table 2

[0128]

[0129] The present invention performs performance testing on the top coating material used in the embodiment, and the test results are shown in Table 3:

[0130] Table 3

[0131]

[0132] The composite coating sample was prepared by referring to the coating process of the long-lasting anti-fouling thermal conductive heat dissipation coating composite coating of Example 1, and the performance test was carried out. The test results are shown in Table 4 and Table 5:

[0133] Table 4

[0134]

[0135] Table 5

[0136]

[0137] Comparative Example

[0138] The common coating of the present invention refers to coating materials including inorganic and metal coatings; organic coatings; organic-inorganic hybrid coatings, etc. Taking organic coatings as an example, a common acrylic anticorrosive coating practical formula, in terms of the percentage of total mass, includes: 30% self-crosslinking acrylic resin (Sanmu 1206), 15% titanium dioxide (TIR588), 5% carbon black, 20% rust-proof pigment iron titanium powder and auxiliary dispersant (Zhanxin). VXW 6208 / 60) 1%, dispersion medium: xylene 20%, n-butanol 9%, each component is mixed and dispersed into a uniform fluid, and coated with a suitable air spray gun, with a coating thickness of 100μm, to convert it into a suitable coating and coating film to obtain a common coating.

[0139] The main performance parameters of common coatings and test results are shown in Table 6 and Table 7

[0140] Table 6

[0141]

[0142] Table 7

[0143]

[0144] Figure 1 Schematic diagram of the hydrophobic sample plates of the composite coating prepared in Example 1 of the present invention and the ordinary coating prepared in the comparative example; wherein, the upper small plate is the hydrophobic sample plate of the long-lasting anti-fouling, thermally conductive and heat-dissipating composite coating, and the lower large plate is the hydrophilic sample plate of the ordinary anti-corrosion coating. Visual inspection of the picture clearly shows that the contact angle of the small plate is much larger than the contact angle of the large plate, indicating that water is difficult to adhere to the surface of the small plate, but easier to adhere to the surface of the large plate, thereby judging that the small sample plate has better anti-fouling performance.

[0145] By comparing the test results of ordinary coating performance parameters in Table 6 and Table 7 with the test results of the performance of long-lasting anti-fouling thermal conductive and heat dissipation coating composite coating in Table 3 and Table 5, the following conclusions can be drawn: Compared with ordinary coatings, the long-lasting anti-fouling thermal conductive and heat dissipation composite coating has excellent performance in both thermal conductivity and heat dissipation and long-term anti-fouling, achieving the effect of long-lasting anti-fouling thermal conductive and heat dissipation.

[0146] It can be seen from the above embodiments that the present invention provides a long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating, including a primer and a top coating; based on the total mass of 100%, the primer includes 15-25% of an organic polysilazane precursor, 4.5-5.5% of a fluorosilicone resin, 1-2% of a graphene material, 0.5-1.5% of a carbon nanotube, 0.5-1.5% of insulating carbon black, 5-10% of a whisker material, 5-10% of a nanoscale heat-dissipating filler, 30-40% of a micron-scale heat-dissipating filler, 0.5-2% of a coupling agent, 2-4% of a non-ionic polymer dispersant, 6-10% of a pyrrolidone material, 1-2.5% of other additives and the remainder of a solvent. The present invention adopts a composite modification of an organic polysilazane precursor with long-term anti-fouling, hydrophobic and oleophobic properties and a fluorosilicone resin, and then uniformly mixes with graphene materials with high thermal conductivity and high emissivity, carbon nanotubes and other nano-carbon materials and nano-scale heat dissipation fillers, and micron-scale heat dissipation fillers to form a dense long-term anti-fouling and heat dissipation coating, so that the coating has a continuous, mutually contacting heat-conducting network chain and heat-conducting path, so that the bottom coating has both excellent long-term anti-fouling and heat dissipation functions, and thus obtains a composite coating with excellent anti-fouling and heat dissipation. The experimental results show that the thermal conductivity of the composite coating is 3.534-4.255W / (mk); at 25°C, the infrared thermal emissivity is 0.93-0.96; the hydrophobic contact angle is 110°-120°, and the rolling contact angle is 8°-10°; the dirt is easy to remove.

[0147] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A long-lasting anti-fouling thermal conductive heat dissipation coating composite coating, comprising a primer and a topcoat; Based on 100% of the total mass, the primer layer includes 15-25% of an organic polysilazane precursor, 4.5-5.5% of a fluorosilicone resin, 1-2% of a graphene material, 0.5-1.5% of a carbon nanotube, 0.5-1.5% of an insulating carbon black, 5-10% of a whisker material, 5-10% of a nanoscale heat dissipation filler, 30-40% of a micron-scale heat dissipation filler, 0.5-2% of a coupling agent, 2-4% of a nonionic polymer dispersant, 6-10% of a pyrrolidone material, 2-4% of other additives, and the remainder of a solvent.

2. The long-lasting anti-fouling thermal conductive heat dissipation coating composite coating according to claim 1 is characterized in that: The organic polysilazane precursor is selected from one or more of methyl hydrogen silazane, hexamethylcyclotrisilazane, octamethylcyclotetrasilazane, methyl vinyl silazane, vinyl polysilazane, methyl polysilazane and silicone rubber polysilazane.

3. The long-lasting anti-fouling thermal conductive heat dissipation coating composite coating according to claim 1 is characterized in that: The nonionic polymer dispersant is selected from one or more of polyether super dispersants, polyacrylic acid super dispersants and polyolefin super dispersants; The coupling agent is selected from one or more of a titanate coupling agent, a polysiloxane coupling agent, a chromate coupling agent and an aluminate coupling agent; The pyrrolidone material is selected from N-methylpyrrolidone solvent and / or polyvinylpyrrolidone solution; The whisker material is selected from one or more of whisker silicon, aluminum oxide whisker, silicon carbide whisker, boron carbide whisker, zirconium dioxide whisker, aluminum nitride whisker and silicon nitride whisker.

4. The long-lasting anti-fouling thermally conductive and heat-dissipating coating according to claim 1 is characterized in that: The nanoscale heat dissipation filler is selected from one or more of spinel pigments, aluminum nitride nanoscale materials, aluminum oxide nanoscale materials, silicon nitride nanoscale materials, boron nitride nanoscale materials, silicon carbide nanoscale materials, magnesium oxide nanoscale materials, zinc oxide nanoscale materials, silicon oxide nanoscale materials, barium titanate nanoscale materials and cerium dioxide nanoscale materials; The micron-sized heat dissipation filler is selected from one or more of an aluminum oxide micron-sized filler, a boron nitride micron-sized filler and a silicon carbide micron-sized filler; The other additives include one or more of fluorosilicone surfactants, fluorosilicone leveling agents, thixotropic thickeners and defoamers; The solvent is selected from one or more of aromatic hydrocarbon solvents, alcohol ether solvents and ester solvents.

5. The long-lasting anti-fouling thermal conductive heat dissipation coating composite coating according to claim 1 is characterized in that: The total thickness of the top coating and the primer is 10-15 μm.

6. The long-lasting anti-fouling thermal conductive and heat dissipating coating composite coating according to any one of claims 1 to 5, characterized in that: Calculated by mass fraction, the raw materials for preparing the top coating include 70-80% fluorosilicone resin, 1-2% nano anti-graffiti additive, 1-5% other additives and the balance solvent.

7. The long-lasting anti-fouling thermally conductive and heat-dissipating coating composite coating according to claim 6 is characterized in that: The fluorosilicone resin is a self-crosslinking perfluorinated modified polysiloxane resin; The nano anti-graffiti additive is a nano anatase titanium dioxide material; The other additives are selected from one or more of fluorosilicone leveling agents, defoaming agents and thixotropic thickeners; The solvent is selected from one or more of aromatic hydrocarbon solvents, ester solvents and alcohol ether solvents.

8. A method for preparing the long-lasting anti-fouling thermal conductive and heat dissipating coating composite coating according to claim 1, comprising the following steps: Mixing part of the organic polysilazane precursor, fluorosilicone resin, nonionic polymer dispersant, coupling agent, pyrrolidone material, part of the solvent, graphene material, insulating carbon black and carbon nanotubes, dispersing to obtain a dispersed slurry, grinding to a fineness of less than 5 μm, to obtain a first grinding slurry; The first grinding slurry and the whisker material, the nano-scale heat dissipation filler, and the micron-scale heat dissipation filler are further ground to a fineness of less than 15 μm to obtain a second grinding slurry; The second grinding slurry is mixed with the remaining organopolysilazane precursor, other additives, and the remaining solvent to obtain a primer coating; The base coating is electrostatically sprayed and then covered with a top coating to obtain a long-lasting anti-fouling, thermally conductive and heat-dissipating composite coating.

9. The preparation method according to claim 8, characterized in that: The electrostatic spraying comprises: The coating process adopts high-voltage electrostatic spraying technology. The primer coating component is sprayed first, and the charged atomized particles are oriented using the electric field effect and the spray gun to shape the micro-nano papillary structure of the coating.

10. The preparation method according to claim 9, characterized in that: The caliber of the spray gun is 0.4-0.6 mm.